High-toughness heat-resistant self-repairing organic silicon elastomer material and preparation method thereof
By introducing a high crosslinking network of imine bonds, borate ester bonds and amide bonds into silicone elastomers, combined with metal ion coordination bonds, the problems of degradation in performance and insufficient mechanical properties of silicone elastomers in high temperature environments are solved. , realizes high toughness, heat resistance and self-repair capabilities, and is suitable for applications in harsh environments.
Patent Information
- Application Number
- CN202411407485.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
AI Technical Summary
The performance of existing silicone elastomers is degraded in high temperature environments, and traditional self-repair methods sacrifice the heat resistance of the material, making it difficult to apply in harsh environments such as aerospace, and the mechanical properties of the material are insufficient, which limits its widespread use.
By reacting the pendant methylaminopropyl polysiloxane with a phenylboric acid derivative, a metal salt and terephthalaldehyde sequentially, a high crosslinking network polymer with imine bonds, borate ester bonds and amide bonds, combined with Metal ion coordination bonds are designed to design high toughness, heat resistance, self-repairing silicone elastomer materials.
The material has heat resistance and high toughness above 350℃, the elongation of break is greater than 1200%, the room temperature self-repair efficiency is as high as 98%, and it has repeatable processing properties, which significantly improves the self-repair performance and mechanical properties of the material.
Smart Images

Figure CN119241850A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-toughness, heat-resistant and self-repairable organic silicon elastomer material and a preparation method thereof. Background Art
[0002] Silicone elastomers are known for their unique organic-inorganic hybrid molecular structure, which gives them a range of outstanding properties, including excellent weather resistance, excellent aging resistance, and excellent electrical insulation. These properties make silicone elastomers play a vital role in many fields, covering a wide range of industries from transportation to healthcare to defense and electronic equipment. However, despite the significant advantages of silicone elastomers in performance, they still face challenges in practical applications. When materials suffer physical damage such as tearing, puncture or twisting, their performance is often affected, resulting in a shortened service life. This situation not only causes a waste of resources, but also may burden the environment. To solve this problem, scientists are exploring the integration of intrinsic self-healing technology into silicone elastomers. By giving materials the ability to self-heal, their service life can be significantly extended and the frequency of replacement due to damage can be reduced. This innovation can not only improve the economic efficiency of materials, but also reduce their impact on the environment, thus showing great significance and potential in a wide range of applications.
[0003] Silicone elastomers play a vital role in aerospace, electronics, automobile and other industries due to their excellent electrical insulation and high temperature resistance. The polysiloxane segments of these materials themselves have excellent heat resistance. However, traditional silicone elastomers are usually limited to temperatures below 200°C when used for a long time. In the study of silicone elastomers that pursue self-healing ability, researchers often enhance their self-healing properties by introducing chain extenders containing longer hydrocarbon chains such as polyurethane and isocyanate. However, this method may sacrifice some of the heat resistance of the material. Under high temperature conditions, the material is susceptible to thermal depolymerization, ionic degradation and thermal oxidation degradation, which will lead to a significant decrease in performance. Especially in the field of aerospace, the operating environment of equipment is often extremely changeable, and the material needs to be able to work stably under extremely high or low temperature conditions. High-temperature resistant silicone elastomers can withstand high temperatures above 300°C while maintaining their mechanical and physical properties under low temperature conditions, which plays an irreplaceable role in aerospace equipment. In view of this, it is particularly urgent to develop a silicone elastomer material that has both high toughness and high temperature resistance, as well as self-healing ability and repeatability. Such materials will greatly improve the reliability and durability of products in harsh environments, reduce maintenance costs and environmental impacts caused by material damage, and are of great significance for promoting technological progress and sustainable development in related industries. At the same time, traditional silicone elastomers have weak mechanical properties and are difficult to apply to some application fields that have high requirements for materials. Silicone elastomers are usually cross-linked by irreversible covalent bonds, which makes them difficult to recycle and causes a lot of waste of resources. Therefore, preparing a highly tough, heat-resistant, self-healing, and reprocessable silicone elastomer is a major challenge and urgent requirement currently facing the research field of silicone elastomers.
[0004] In recent years, scientists have been committed to developing silicone elastomers with self-healing properties by embedding functional small molecules with chemical bonds and physical bonds into the polysiloxane polymer skeleton. This strategy has significantly broadened the application prospects of silicone elastomers. In the past decade, researchers have successfully made breakthroughs in the field of self-healing silicone materials by introducing reversible dynamic bonds such as hydrogen bonds, boron ester bonds, Diels-Alder adducts and coordination bonds. The introduction of these dynamic bonds greatly enhances the self-healing ability of the material, but it also brings some challenges, such as weakening the mechanical properties of the material or reducing the heat resistance. Although a few studies have reported the introduction of multiple dynamic bonds into silicone elastomers to prepare multifunctional materials, it is still challenging to achieve a comprehensive high-performance silicone elastomer. Most existing materials can only perform well in one or two aspects. In patent CN113150284B, Huang Yawen et al. disclosed a triple-repaired double-crosslinked polysiloxane super-hydrophobic elastomer and its preparation method. The material is prepared from (2-formylphenylboronic acid) zinc chloride, side-chain amino polysiloxane and glutaraldehyde. The obtained material has no borate ester bond, but exists in the form of boron hydroxyl and zinc ion complex. The material shows its excellent triple repair performance (mechanical performance repair, super-hydrophobic elastomer structural rupture, needle piercing repair and surface low surface energy material repair), but its mechanical properties are still limited, with a tensile strength of 0.51MPa and an elongation at break of only 196%, which limits its use in certain specific application fields. Zou Huawei et al. disclosed a heat-resistant elastomer that can quickly self-repair at room temperature and its preparation method and application in patent application CN110551269A. This elastomer is made of hydroxypropyl-terminated polydimethylsiloxane, isocyanate and bisaminodisulfide chain extender, showing excellent heat resistance and room temperature self-healing properties. However, its mechanical properties are not satisfactory, with a maximum tensile strength of only 1.2MPa, a maximum elongation at break of 63.35%, and a repair efficiency of only 73.26% at 25°C for 72h, which limits its application in a wider range of fields. In another patent application CN110563922A, Zou Huawei et al. disclosed a chemically cross-linked high-performance room temperature rapid self-healing flexible material and its preparation method and use. The material is made of hydroxypropyl-terminated polydimethylsiloxane, isocyanate, a cross-linking agent and a chain extender. Although it has a high self-healing efficiency at room temperature, its mechanical properties are still limited, with a maximum tensile strength of about 2.0MPa and a maximum elongation at break of about 90%, which limits its use in specific application fields. Summary of the invention
[0005] The invention provides a high-toughness, heat-resistant and self-repairable organic silicon elastomer material and a preparation method thereof.
[0006] [1] A high-toughness, heat-resistant and self-healing silicone elastomer material is obtained by sequentially reacting side-methylaminopropyl polysiloxane with a phenylboronic acid derivative, a metal salt and terephthalaldehyde and then curing the resultant.
[0007] The number average molecular weight (Mn) of the side methylaminopropyl polysiloxane is 2000 to 30000 g mol -1 , further can be 8000~30000g mol -1 , for example 15000 g mol -1 , 20000g mol -1 , 25000 g mol -1 wait.
[0008] The side methylaminopropyl polysiloxane has the structure shown below:
[0009]
[0010] Among them, a / (a+b) = 90% to 99%. That is, b / (a+b) = 1% to 10%, which can be recorded as amino (-NH 2 )'s molar content, for example, may be 2%, 3%, 5%, 6%, 8%, etc.
[0011] The phenylboronic acid derivatives include one or more of 2-formylphenylboronic acid, 4-formylphenylboronic acid, 2-carboxylphenylboronic acid, and 4-carboxylphenylboronic acid.
[0012] The metal salt is used to provide metal ions, and the metal ions include Fe 2+ , Fe 3+ 、Zn 2+ One or more of .
[0013] In some preferred examples, the molecular weight distribution of the pendant methylaminopropyl polysiloxane is less than 1.5.
[0014] The high-toughness, heat-resistant and self-repairable organic silicone elastomer material has an imide bond and a borate bond, or an imide bond, a borate bond and an amide bond. The borate bond can be specifically represented by B and O arranged at intervals. 3 O 3 Six-membered ring structure (borane-oxygen six-ring).
[0015] In the high-toughness, heat-resistant and self-repairable organic silicone elastomer material, the amino group in the side methylaminopropyl polysiloxane forms a coordination bond with the metal ion.
[0016] In some embodiments, the molar ratio of the pendant methylaminopropyl polysiloxane to the phenylboric acid derivative, the metal ion, and the terephthalaldehyde is 1:(1-10):(1-10):(1-5).
[0017] In some embodiments, the metal salt may include FeCl 3 、FeCl 2 、ZnCl 2 、FeSO 4 , Fe 2 (SO 4 ) 3 、ZnSO 4 、Zn(ClO 4 ) 2 One or more of .
[0018] The curing temperature will affect the degree of entanglement of the molecular chains in the polymer, resulting in different mechanical strengths of the elastomer. In some preferred embodiments, the curing temperature may be 60 to 120°C, and further may be 90 to 100°C.
[0019] In some embodiments, the toughness of the high-toughness heat-resistant self-repairable silicone elastomer material is greater than 20 MJ m -3 , under optimal conditions, greater than 24 MJ m -3 , the elongation at break is greater than 1200%, not less than 1500% under preferred conditions, the heat resistance temperature is greater than 350°C, the self-repair efficiency of the tensile strength after 24 hours of self-repair at room temperature is not less than 94%, not less than 98% under preferred conditions, and the repeatable processing efficiency of the elongation at break dimension is greater than 97%.
[0020] In the present invention, the toughness can be calculated according to the method known in the art, that is, calculated based on the area under the stress-strain curve.
[0021] In the present invention, the specific operation of the repeated processing can be to press the broken high-toughness heat-resistant self-repairable silicone elastomer material under a certain pressure for a period of time to complete the repair process. Further, the certain pressure can be 10 to 15 MPa, and the period of time can be 10 to 20 minutes.
[0022] Unless otherwise specified, in the present invention:
[0023] The self-healing efficiency is defined as the ratio of the tensile strength of the initial sample to that of the sample after self-healing;
[0024] The reproducible processing efficiency is defined as the ratio of the elongation at break of the initial sample and the reprocessed sample.
[0025] [2] The method for preparing the high-toughness, heat-resistant and self-repairable silicone elastomer material according to [1] comprises:
[0026] Step 1: in a first solution, a side methylaminopropyl polysiloxane reacts with a phenylboronic acid derivative to obtain a polymer 1;
[0027] Step 2: In a second solution, polymer 1 reacts with a metal salt to obtain polymer 2;
[0028] Step 3: In the third solution, polymer 2 reacts with terephthalaldehyde, and then the solvent is removed and cured to obtain the high-toughness, heat-resistant and self-repairable organic silicone elastomer material.
[0029] In step 1, the solvent of the first solution may include tetrahydrofuran.
[0030] In step 1, the reaction temperature of the side methylaminopropyl polysiloxane and the phenylboronic acid derivative can be 30 to 80° C., further can be 40 to 50° C., and the reaction time can be 4 to 10 hours, further can be 6 to 7 hours.
[0031] In step 2, the solvent of the second solution may include tetrahydrofuran.
[0032] In step 2, the reaction temperature of polymer 1 and metal salt can be room temperature or 25-30° C., and the reaction time can be 10-12 h.
[0033] In step 2, the concentration of the metal salt in the second solution may be 0.1 to 0.4 g mL -1 , e.g. 0.2 gmL -1 , 0.3 g mL -1 wait.
[0034] In step three, the solvent of the third solution may include tetrahydrofuran.
[0035] In step 3, the reaction temperature of polymer 2 and terephthalaldehyde can be 30-100° C., further can be 40-60° C., and the reaction time can be 2-6 hours, further can be 3-4 hours.
[0036] In step 3, the solvent can be removed by volatilizing the solvent at room temperature. Furthermore, the time for volatilizing the solvent at room temperature can be 10 to 12 hours.
[0037] In step 3, the curing temperature affects the degree of entanglement of the molecular chains in the polymer, resulting in different mechanical strengths of the elastomer. In some preferred embodiments, the curing temperature may be 60 to 120°C, further 90 to 100°C, and the curing time may be 4 to 12 hours, further 8 to 10 hours.
[0038] The invention forms a cross-linked network polymer having a borate bond (borate bond and amide bond) by reacting a side chain aminopropyl group of a side methylaminopropyl polysiloxane with an aldehyde group (carboxyl group) of formylphenylboronic acid (carboxylphenylboronic acid), then adds metal ions into the polymer to form a coordination bond with an amino group in the highly cross-linked network polymer, and finally forms a highly cross-linked network polymer having an imine bond by reacting a side chain aminopropyl group of the side methylaminopropyl polysiloxane with an aldehyde group of terephthalaldehyde.
[0039] In the technical solution of the present invention, the copolymer is prepared in three steps to design and construct multiple bonds in the network to achieve multiple properties of the material. In the network, the side amino group on the side methylaminopropyl polysiloxane forms a strong coordination effect with the metal ion, and the side amino group on the side methylaminopropyl polysiloxane reacts with terephthalaldehyde and formyl / carboxylphenylboronic acid to introduce dynamic imine bonds / imine bonds + amide bonds and borate bonds into the polysiloxane system. Under the action of force, the coordination bond, imine bond / imine bond + amide bond and borate bond are destroyed, and after the external force is removed, the coordination bond, imine bond / imine bond + amide bond and borate bond are re-formed, so that the material obtains self-healing properties.
[0040] The elastomer of the present invention has high toughness, heat resistance, repeatable processing performance and room temperature self-repairing ability. It can quickly complete self-repair at room temperature with high repair efficiency. It also has good thermal stability, good toughness and can be repeatedly processed.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The silicone elastomer prepared by the present invention is designed with more reactive active groups in its structure, and an imine bond / imine bond + amide bond, borate bond and coordination bond are simultaneously introduced into the structure by a simple preparation process, thereby constructing a new elastomer structure with multiple bond effects and greatly improving the self-healing performance of the material, so that the material can repair scratches at room temperature.
[0043] 2. The high-toughness, heat-resistant, self-repairable and re-processable silicone elastomer prepared by the present invention has a heat-resistant temperature of up to 350°C or above, achieving high temperature resistance.
[0044] 3. Due to the introduction of multiple dynamic bonds, the material also has high toughness and can be repeatedly processed. The elongation at break is higher than 1200%, the highest elongation at break can reach 3500%, and the repeated processing efficiency can reach more than 98%.
[0045] 4. The raw materials of the present invention are simple and easy to obtain, and are all commercial products or can be prepared by referring to the existing technology combined with common knowledge in the field. The synthesis process is simple and the cost is low. It is easy to mass produce and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is the infrared spectrum of the high-toughness, heat-resistant, self-repairable and re-processable silicone elastomer prepared in Example 1 of the present invention.
[0047] Figure 2 This is a thermogravimetric analysis (TGA and DTG) curve of the high-toughness, heat-resistant, self-repairable and re-processable silicone elastomer prepared in Example 1 of the present invention.
[0048] Figure 3 These are self-healing photos of the silicone elastomer in Example 1 of the present invention taken under an optical microscope at different times after being cut by a blade.
[0049] Figure 4 This is a stress-strain curve diagram of different repair times of the silicone elastomer after being cut by a blade in Example 1 of the present invention.
[0050] Figure 5 Schematic diagram and photograph of the repeated processing flow of the silicone elastomer after heat pressing in Example 1 of the present invention.
[0051] Figure 6 1 is a stress-strain curve diagram of the silicone elastomer after different processing times in Example 1 of the present invention. DETAILED DESCRIPTION
[0052] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0053] The side methylaminopropyl polysiloxanes involved in the specific implementation manner all have the following structure:
[0054]
[0055] Here, the amino content is represented by b / (a+b).
[0056] The side methylaminopropyl polysiloxane involved in the specific embodiment can be prepared according to the common knowledge in the art by referring to the similar method in the prior art or the exemplary method described below:
[0057] Add octamethylcyclotetrasiloxane, aminopropylmethyldimethoxysilane, tetramethylammonium hydroxide alkali glue, deionized water, and low-viscosity methyl silicone oil (100cp) to the reaction vessel, heat to 85-95°C in a nitrogen atmosphere and balance for 3-5 hours, then vacuum remove the water and generated methanol in the reaction system for about 1 hour, and continue to balance for 5-7 hours. Then quickly heat to 130-150°C and maintain for 0.5-1 hour to decompose and inactivate the catalyst. Finally, remove the small molecular low-boiling substances in the reaction system under reduced pressure at a temperature of 160-180°C to obtain a colorless, transparent, viscous liquid, which is the prepared side methylaminopropyl polysiloxane.
[0058] In the above-described method, the side methylaminopropyl polysiloxane with the desired amino content, molecular weight and molecular weight distribution can be obtained by adjusting the amount of raw materials, reaction parameters (such as temperature, time, etc.). For example, the ratio of octamethylcyclotetrasiloxane, aminopropylmethyldimethoxysilane, tetramethylammonium hydroxide alkali glue, deionized water, and low-viscosity methyl silicone oil can be 78-82g: 1-15g: 1.7-2.1g: 0.4-4.5mL: 1.7-2.1g.
[0059] Example 1
[0060] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 30000 g mol -1 , amino content 8 mol%), fully dissolved in 200 mL of tetrahydrofuran, add 4.5 g of 2-formylphenylboronic acid (dissolved in 225 mL of tetrahydrofuran), mix well and place at 40°C for 6 h with stirring to react, then take out;
[0061] 2) Add 0.2 g / mL anhydrous zinc chloride (5.5 g) tetrahydrofuran solution to the obtained polymer, stir evenly for 10 hours and take it out after it fully reacts;
[0062] 3) Finally, 2.2 g of terephthalaldehyde (dissolved in 110 mL of tetrahydrofuran) was added to the polymer, mixed evenly, and stirred at 50 °C for 3 h. Then, the mixture was poured into a mold and placed in a fume hood for leveling at room temperature. After the tetrahydrofuran evaporated, the mixture was moved to a 90 °C vacuum oven and dried for 12 h before demolding to obtain a high-toughness, heat-resistant, self-repairable, and reproducible silicone elastomer with a toughness of 24.6 MJ m -3 .
[0063] Example 2
[0064] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 25000 g mol -1, amino content 6 mol%), fully dissolved in 200 mL of tetrahydrofuran, add 4.5 g of 4-formylphenylboronic acid (dissolved in 225 mL of tetrahydrofuran), mix well and place at 50°C for 7 h with stirring to react, then take out;
[0065] 2) Add 0.2 g / mL anhydrous ferric chloride (5.5 g) tetrahydrofuran solution to the obtained polymer, stir evenly for 12 hours and take it out after it fully reacts;
[0066] 3) Finally, add 1 g of terephthalaldehyde (dissolved in 50 mL of tetrahydrofuran) to the polymer, mix well, place at 50° C. for stirring and reaction for 3 h, pour into a mold, place in a fume hood for leveling at room temperature, wait for the tetrahydrofuran to evaporate, move to a 120° C. vacuum oven for drying for 12 h, and then demold to obtain a silicone elastomer.
[0067] Example 3
[0068] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 20000 g mol -1 , amino content 5 mol%), fully dissolved in 200 mL of tetrahydrofuran, add 3 g of 2-carboxyphenylboronic acid (dissolved in 150 mL of tetrahydrofuran), mix well and place at 40°C for 7 h with stirring for reaction and take out;
[0069] 2) Add 0.1 g / mL anhydrous zinc chloride (8.1 g) tetrahydrofuran solution to the obtained polymer, stir evenly for 10 h and take it out after it fully reacts;
[0070] 3) Finally, add 1 g of terephthalaldehyde (dissolved in 50 mL of tetrahydrofuran) to the polymer, mix well, place at 50°C for stirring and reaction for 4 hours, pour into a mold, place in a fume hood for leveling at room temperature, wait for the tetrahydrofuran to evaporate, move to a 100°C vacuum oven for drying for 12 hours, and then demold to obtain a silicone elastomer.
[0071] Example 4
[0072] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 8000 g mol -1 , amino content 2 mol%), fully dissolved in 200 mL of tetrahydrofuran, add 5 g of 4-carboxyphenylboric acid (dissolved in 250 mL of tetrahydrofuran), mix well and place at 40°C for 7 h with stirring for reaction and take out;
[0073] 2) Add 0.3 g / mL anhydrous ferrous chloride (7.5 g) tetrahydrofuran solution to the obtained polymer, stir evenly for 11 hours and take it out after it fully reacts;
[0074] 3) Finally, add 2 g of terephthalaldehyde (dissolved in 100 mL of tetrahydrofuran) to the polymer, mix well, place at 50° C. for stirring and reaction for 3 h, pour into a mold, place in a fume hood for leveling at room temperature, wait for the tetrahydrofuran to evaporate, move to a 90° C. vacuum oven for drying for 12 h, and then demold to obtain a silicone elastomer.
[0075] Example 5
[0076] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 15000 g mol -1 , amino content 3 mol%), fully dissolved in 200 mL of tetrahydrofuran, add 8 g of 2-formylphenylboronic acid (dissolved in 400 mL of tetrahydrofuran), mix well and place at 40°C for 6 h with stirring to react, then take out;
[0077] 2) Add 0.1 g / mL anhydrous zinc sulfate (7.5 g) tetrahydrofuran solution to the obtained polymer, stir evenly for 10 hours and take it out after it fully reacts;
[0078] 3) Finally, add 2 g of terephthalaldehyde (dissolved in 100 mL of tetrahydrofuran) to the polymer, mix well, place at 60° C. for stirring and reaction for 3 h, pour into a mold, place in a fume hood for leveling at room temperature, wait for the tetrahydrofuran to evaporate, move to a 90° C. vacuum oven for drying for 12 h, and then demold to obtain a silicone elastomer.
[0079] The composition of the silicone elastomers of Examples 1 to 5, the process parameters of the specific preparation process and the performance test results of the final products are shown in Table 1. In Table 1, the test method and result acquisition of the 24-hour repair efficiency at room temperature are introduced as follows: a scratch is made in the middle of the elastomer sample with a disposable blade, and then kept at room temperature for 24 hours, the tensile strength is measured, and the percentage value of the initial tensile strength of the elastomer sample is calculated.
[0080] Table 1
[0081]
[0082] Comparative Example 1
[0083] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 30000 g mol -1 , amino content 8mol%), fully dissolved in 200mL tetrahydrofuran, add 4.5g 2-formylphenylboronic acid (dissolved in 225mL tetrahydrofuran), mix well and place at 40°C for 6h after stirring and reaction, then take out;
[0084] 2) Add 2.2 g of terephthalaldehyde (dissolved in 110 mL of tetrahydrofuran) to the obtained polymer, mix well, place at 50 °C for 3 h, stir and react, pour into a mold, place in a fume hood at room temperature for leveling, wait for the tetrahydrofuran to evaporate, move to a 90 °C vacuum oven for 12 h, and then demold. The obtained elastomer has poor toughness, less than 0.1 MJ m -3 This is because the relatively weak coordination bonds are first broken under stress during the stretching process, and dissipate most of the energy as "sacrificial bonds", so the coordination bonds mainly improve the toughness and ductility of the material. Comparative Example 1 has no coordination bonds between metal ions and amino groups, and has poor toughness.
[0085] Comparative Example 2
[0086] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 30000 g mol -1 , amino content 8 mol%), fully dissolved in 200 mL of tetrahydrofuran, add 0.2 g / mL anhydrous zinc chloride (5.5 g) tetrahydrofuran solution, stir evenly for 10 h, and then take out after it fully reacts;
[0087] 2) Finally, 4.5g of 2-formylphenylboronic acid (dissolved in 225mL tetrahydrofuran) was added to the polymer, and the mixture was stirred and reacted at 40°C for 6h, poured into a mold and placed in a fume hood for leveling at room temperature, and after the tetrahydrofuran volatilized, it was moved to a 90°C vacuum oven and dried for 12h before demoulding. The obtained elastomer had poor tensile strength, and the maximum tensile strength was less than 0.7MPa. Comparative Example 2 had no imine bond between terephthalaldehyde and amino, and had poor strength. This is because the number of imine bonds constructed by the formyl group and amino group of 2-formylphenylboronic acid was not enough to obtain higher strength, and the further reason was that the strong chemical bond was relatively not easy to break, and the cross-linked network of the elastomer could be stabilized to ensure its integrity, thereby enhancing the mechanical strength of the material.
[0088] Comparative Example 3
[0089] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 30000 g mol -1 , amino content 8 mol%), fully dissolved in 200 mL of tetrahydrofuran, 2.2 g of terephthalaldehyde (dissolved in 110 mL of tetrahydrofuran) was added, mixed evenly and placed at 50°C with stirring for 3 hours. After taking out, it was found that the material had gelled and could not be operated in the next step, and ultimately the elastomer could not be obtained.
[0090] Comparative Example 4
[0091] 1) Take 100 g of side methylaminopropyl polysiloxane (Mn = 30000 g mol -1, amino content 8 mol%), fully dissolved in 200 mL of tetrahydrofuran, add 4.5 g of 2-formylphenylboronic acid (dissolved in 225 mL of tetrahydrofuran), mix well and place at 40°C for 6 h with stirring to react, then take out;
[0092] 2) Add 0.2 g / mL anhydrous zinc chloride (5.5 g) tetrahydrofuran solution to the obtained polymer, stir evenly for 10 hours and take it out after it fully reacts;
[0093] 3) Finally, add 2.2g of terephthalaldehyde (dissolved in 110mL of tetrahydrofuran) to the polymer, mix well, place at 50°C for 3h, stir and react, pour into the mold, place in a fume hood at room temperature for leveling, wait for the tetrahydrofuran to evaporate, move to a 150°C vacuum oven for 12h, and then demold. Due to the high curing and cross-linking temperature, the elastomer loses its mechanical properties and becomes brittle.
[0094] Figure 1 This is the infrared spectrum of the highly tough, heat-resistant, self-repairable and reproducible silicone elastomer prepared in Example 1 of the present invention. -1 In the wave number range, 1690 cm -l The aldehyde absorption peak at 1645 cm -1 The C=N stretching vibration absorption peak at 696 cm indicates that the aminopropyl group of the methylaminopropyl polysiloxane successfully reacts with the aldehyde group of terephthalaldehyde and formylphenylboronic acid. -1 B 3 O 3 The disappearance of the absorption peak and the boron hydroxyl peak indicates that the boron hydroxyl of formylphenylboronic acid was successfully condensed to form a hexacyclic boron oxide.
[0095] Figure 2 The TGA and DTG curves of the high-toughness, heat-resistant, self-repairable and reproducible silicone elastomer prepared in Example 1 of the present invention are shown in FIG. From the data in the figure, it can be seen that the temperature at which the mass loss is 5 wt% is 355° C., and the residual weight at 800° C. is 19%.
[0096] Figure 3 Schematic diagram of the self-repair of the high-toughness, heat-resistant, self-repairable and re-processable organosilicon elastomer prepared in Example 1 of the present invention under an optical microscope. A scratch was made in the middle of the elastomer sample prepared in Example 1 with a disposable blade, and then kept at room temperature for 24 hours. The repair result is as follows: Figure 3 shown.
[0097] Figure 4The stress-strain curves of different repair times of the high-toughness, heat-resistant, self-repairing and re-processable silicone elastomer prepared in Example 1 of the present invention are shown in FIG. 1 , wherein the Original label represents the initial sample. A scratch is made in the middle of the elastomer sample prepared in Example 1 with a disposable blade, and then placed at room temperature for self-repair. As the self-repair time increases, the self-repair efficiency increases, with a self-repair efficiency of 40% for 1 hour, 77% for 8 hours, and 98% for 24 hours.
[0098] Figure 5 This is a schematic diagram of the repeated processing of the high-toughness, heat-resistant, self-repairable and reprocessable silicone elastomer prepared in Example 1 of the present invention. As can be seen from the figure, after the silicone elastomer is cut into pieces, it can be basically restored to its original state by applying a pressure of 15 MPa for 10 minutes at room temperature. Figure 6 The stress-strain curves of the high-toughness, heat-resistant, self-repairable and reproducible silicone elastomer prepared in Example 1 of the present invention after different processing times in the above manner. After 5 cycles, the tensile strength and elongation at break of the elastomer were 1.34 MPa and 1790%, respectively, recovering to 86% and 98% of the original values, respectively.
[0099] In summary, the present invention has prepared a silicone elastomer that has good toughness, heat resistance, self-healing ability and repeatable processing.
[0100] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A high-toughness, heat-resistant and self-repairable organic silicone elastomer material, characterized in that: The method is obtained by sequentially reacting side methylaminopropyl polysiloxane with phenylboric acid derivatives, metal salts and terephthalaldehyde, followed by curing. The number average molecular weight of the side methylaminopropyl polysiloxane is 2000 to 30000 g mol -1 , further 8000~30000g mol -1 ; The side methylaminopropyl polysiloxane has the structure shown below: Among them, a / (a+b)=90%~99%; The phenylboronic acid derivatives include one or more of 2-formylphenylboronic acid, 4-formylphenylboronic acid, 2-carboxylphenylboronic acid, and 4-carboxylphenylboronic acid; The metal salt is used to provide metal ions, and the metal ions include Fe 2+ , Fe 3+ 、Zn 2+ One or more of .
2. The high-toughness, heat-resistant and self-repairable organic silicon elastomer material according to claim 1, characterized in that: The molecular weight distribution of the pendant methylaminopropyl polysiloxane is less than 1.
5.
3. The high-toughness, heat-resistant and self-repairable organic silicon elastomer material according to claim 1, characterized in that: The high-toughness, heat-resistant and self-repairable organic silicone elastomer material has an imine bond and a borate bond, or an imine bond, a borate bond and an amide bond; In the high-toughness, heat-resistant and self-repairable organic silicone elastomer material, the amino group in the side methylaminopropyl polysiloxane forms a coordination bond with the metal ion.
4. The high-toughness, heat-resistant and self-repairable organic silicon elastomer material according to claim 1, characterized in that: The molar ratio of the side methylaminopropyl polysiloxane to the phenylboric acid derivative, the metal ion and the terephthalaldehyde is 1:(1-10):(1-10):(1-5).
5. The high-toughness, heat-resistant and self-repairable organic silicon elastomer material according to claim 1, characterized in that: The metal salt includes one or more of FeCl3, FeCl2, ZnCl2, FeSO4, Fe2(SO4)3, ZnSO4, and Zn(ClO4)2.
6. The high-toughness, heat-resistant and self-repairable organic silicon elastomer material according to claim 1, characterized in that: The toughness of the high-toughness heat-resistant self-repairable silicone elastomer material is greater than 20 MJ m -3 , the elongation at break is greater than 1200%, the heat resistance temperature is greater than 350°C, the self-repair efficiency of the tensile strength after 24 hours of self-repair at room temperature is not less than 94%, and the repeatable processing efficiency of the elongation at break dimension is greater than 97%.
7. The method for preparing a high-toughness, heat-resistant and self-repairable organic silicon elastomer material according to any one of claims 1 to 6, characterized in that: include: Step 1: in a first solution, a side methylaminopropyl polysiloxane reacts with a phenylboronic acid derivative to obtain a polymer 1; Step 2: In a second solution, polymer 1 reacts with a metal salt to obtain polymer 2; Step 3: In the third solution, polymer 2 reacts with terephthalaldehyde, and then the solvent is removed and cured to obtain the high-toughness, heat-resistant and self-repairable organic silicone elastomer material.
8. The preparation method according to claim 7, characterized in that: In step one: The solvent of the first solution includes tetrahydrofuran; The reaction temperature of the side methylaminopropyl polysiloxane and the phenylboronic acid derivative is 30 to 80° C., further 40 to 50° C., and the reaction time is 4 to 10 hours, further 6 to 7 hours.
9. The preparation method according to claim 7, characterized in that: In step 2: The solvent of the second solution includes tetrahydrofuran; The reaction temperature of polymer 1 and metal salt is room temperature or 25-30°C, and the reaction time is 10-12h; In the second solution, the concentration of the metal salt is 0.1 to 0.4 g mL -1 .
10. The preparation method according to claim 7, characterized in that: In step three: The solvent of the third solution includes tetrahydrofuran; The reaction temperature of polymer 2 and terephthalaldehyde is 30 to 100° C., further 40 to 60° C., and the reaction time is 2 to 6 hours, further 3 to 4 hours; The solvent is removed by volatilizing the solvent at room temperature, and the time for volatilizing the solvent at room temperature is 10 to 12 hours; The curing temperature is 60 to 120° C., further 90 to 100° C., and the curing time is 4 to 12 hours, further 8 to 10 hours.
Citation Information
Cited By
Radiation-resistant self-repairing epoxy resin coating and preparation method thereof
CN120158184A
High-strength flame-retardant aramid fiber composite material and preparation method thereof
CN120666458A
